2019
DOI: 10.1074/jbc.ra119.008485
|View full text |Cite
|
Sign up to set email alerts
|

E3 ubiquitin-protein ligase TRIM21-mediated lysine capture by UBE2E1 reveals substrate-targeting mode of a ubiquitin-conjugating E2

Abstract: This article contains Figs. S1-S7 and Tables S1-S5. The atomic coordinates and structure factors (codes 5LBN and 6FGA) have been deposited in the Protein Data Bank (http://wwpdb.org/). NMR backbone chemical shifts for the UBE2E1 core domain have been deposited in the Biological Magnetic Resonance Data Bank under accession number 27587.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 79 publications
2
13
0
Order By: Relevance
“…A 2D schematic is depicted in Figure 2K and illustrates the proposed structure of the dimeric RPB1–ARMC5–CUL3–RBX1–UBE2E1–UBC complex based on our results and literature. We extracted X-ray crystallographic 3D information of the components in the complex, that is, RPB1, CUL3, RBX1, UBE2E1, and UBC from the Protein Database ( 56–59 ). The 3D structure of ARMC5 has not been resolved but is predicted by AlphaFold ( 39 ).…”
Section: Resultsmentioning
confidence: 99%
“…A 2D schematic is depicted in Figure 2K and illustrates the proposed structure of the dimeric RPB1–ARMC5–CUL3–RBX1–UBE2E1–UBC complex based on our results and literature. We extracted X-ray crystallographic 3D information of the components in the complex, that is, RPB1, CUL3, RBX1, UBE2E1, and UBC from the Protein Database ( 56–59 ). The 3D structure of ARMC5 has not been resolved but is predicted by AlphaFold ( 39 ).…”
Section: Resultsmentioning
confidence: 99%
“…Phosphorylation of S80 displaces the B-box, thereby allowing E2 recruitment to restore TRIM21 ubiquitination activity. Similar to other TRIM RING/E2∼Ub complexes, the crystal structures of TRIM21 with its cognate E2s, UBE2E1 (PDB: 6FGA) [ 30 ] and a UBE2N-Ub conjugate (PDB: 6S53) [ 29 ], show symmetrical complexes surrounding a RING dimer, while in solution the RING is in a monomer-dimer equilibrium. Nevertheless, mutants that impair dimerization (M10E and M10E/M72E) remain active and able to catalyse unanchored K63-linked ubiquitin chain synthesis, UBE2W-primed anchored K63 chain extension and ubiquitin discharge, however less efficiently than the wild-type protein, suggesting that E3 activity may not strictly require a dimeric RING.…”
Section: Regulation Of Trim Ubiquitination Activitymentioning
confidence: 97%
“…We have also shown that endoglin can interact with TRIM21, a protein involved in multiple cell functions. As other members of the TRIM family, TRIM21 can act as a ubiquitination enzyme targeting for degradation different proteins [56,57,58,90]. The TRIM family has been shown to ubiquitinate different components of the TGF-β signaling pathway [55,91], and our results suggest for the first time that TRIM21 may target for degradation the TGF-β auxiliary receptor endoglin.…”
Section: Discussionmentioning
confidence: 63%
“…Unfortunately, little is known about the connection between the TRIM family and the TGF-β auxiliary receptor endoglin of endothelial cells. Among TRIM family members, TRIM21 acts not only as an E3 ubiquitin ligase on different target proteins, but also as a substrate in auto-ubiquitination, both leading to protein degradation [56,57,58]. In addition, TRIM21 is involved in cancer [59,60], inflammation [61,62,63,64], intracellular immunity, and autoimmunity [47,65,66,67].…”
Section: Resultsmentioning
confidence: 99%